EVALUATION OF THE IMPLEMENTATION FOREIGN OFFICIAL TRAVEL (PDLN) POLICIES (CASE STUDY AT THE THE AGENCY FOR MARINE AND FISHERIES EXTENSION AND HUMAN RESOURCES DEVELOPMENT) - Yusuf Qohary; Edy Sutrisno (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Foreign Official Travel (PDLN) serves as a strategic instrument to enhance the capacity of Indonesia’s civil servants and to support the national human resource development agenda. However, the significant state investment allocated to PDLN particularly at the Human Resource Development Agency for Marine Affairs and Fisheries (BPPSDM KP) often faces suboptimal implementation practices, potentially leading to budget inefficiencies and failures in performance accountability. This qualitative case study aims to analyze the implementation gaps in PDLN policy at BPPSDM KP using Merilee S. Grindle’s framework, focusing on the dimensions of Content of Policy and Context of Implementation. The findings show that ineffective implementation is driven by the interaction of two key factors: (1) ambiguity in the Content of Policy, particularly the inconsistent interpretation of financial regulations (PMK) related to the calculation of Daily Allowances (Uang Harian), which repeatedly triggers findings by the Audit Board of Indonesia (BPK); and (2) critical weaknesses in the Context of Implementation, marked by low accountability as reflected in consistently high rates of delayed reporting (above 20% during 2022–2025) and the absence of a Knowledge Management System (KMS) to ensure institutional utilization of PDLN outcomes. To enhance efficiency and performance accountability, this study recommends strengthening a digital KMS and implementing mandatory Cost-Benefit Analysis for every PDLN proposal to ensure an adequate return on investment for the institution.